PENYELESAIAN PUZZLE SUDOKU MENGGUNAKAN ALGORITMA BRUTE FORCE DAN BACKTRACKING - Andreas Yusuf; Hendra Hendra (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2013)
Sudoku games is the most popular Numeric Puzzle Games in the world. This game requires you to fill in the numbers on a blank column matrix with certain regulations. This study will discuss how to solve Sudoku primarily to take advantage of the Brute Force Algorithm and Backtracking by trying all possible contents of the box element of the matrix. This testing process using black box method, where the program uses four levels of Sudoku puzzle consists of three levels of difficulty beginner level, intermediate level, advanced level, expert level, master level. Sudoku generally consists of a table with the number of boxes 9 x 9, which made the area (region) 3 x 3. Questions Beginners and Intermediate is used. Examiners performed by using an Intel Pentium III 550MHz processor with a 1.6 GHz Core2 Duo with clock speed 694ms and 320ms for about the first and second largest known differences exist at the level of the processor.